Profitability, capital intensity and tax avoidance in Indonesia: The effect board of commissioners' competencies - Marsahala, Yoseph Togu; Arieftiara, Dianwicaksih; Lastiningsih, Noegrahini (Journal of Contemporary Accounting, 2020)
This study aims to research the impact of profitability and capital intensity on tax avoidance moderating with the competence of the board of commissioners. Focus of the study is manufacturing companies listed on Indonesia Stock Exchange for 2016-2018 period. The sampling technique was purposive sampling procedure, and hypotheses testing with regression panel data analysis using STATA version 13 application. The results indicate that profitability has a significant effect on tax avoidance, however, capital intensity has no significant effect on tax avoidance. This study documented that the competence of the board of commissioners weaken the effect of profitability on tax avoidance, however, the study failed to document the moderating role of the competence of commissioners on the effect of capital intensity on tax avoidance. This study contributes on enhance the empirical evidence that if companies have a competent board of commissioners, it can monitor managers' tax avoidance activities, thus managers will decrease the intensity of tax avoidance based on company profitability.